Finite element modelling of soil nailing inclination effect on slope stability: Cibeureum slope case study - Azmi Aufa Iftikhar; Hanindya Kusuma Artati (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2024)
On November 21, 2022, a 5.6 magnitude earthquake caused a landslide on one of the slopes in Cibeureum, Cianjur district. To repair the slope, reinforcement is necessary to achieve stability values that can withstand future earthquakes. One method for enhancing slope stability is soil nailing. Various soil nailing installation angles were analyzed to find the optimal design for the Cibeureum slope. Using the Plaxis 2D V20 program, the safety factor of the original slope without an earthquake was found to be 1.62. Increasing the installation angle of the soil nails from 10°, 15°, to 20° improved the safety factor, but the increase was not significant because the initial installation point was far from the slip line, requiring a nail length of 50 meters. The best configuration, yielding the highest safety value, was achieved with a modified slope angle of 19° and soil nails with a 50 m length installed at a 20° angle. This configuration produced a safety factor of 2.55 without an earthquake and 1.102 with an earthquake, as calculated using the Plaxis 2D V20 program.